“Incorporating Traditional Games into Art Education to Foster Creativity in Children” - Xidoyeva Mahliyo Bozor qizi (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article examines how incorporating traditional national games into art education fosters creativity in children. It highlights the pedagogical and aesthetic benefits of using game-based activities to enhance compositional skills, visual literacy, and emotional expression. The study also provides practical strategies for teachers to integrate traditional games into fine arts lessons.